Comparative evaluation of the efficacy of topical amlexanox 5% oral paste and triamcinolone acetonide 0.1% oral paste in the treatment of Recurrent Aphthous Stomatitis (RAS) - K Shrivastava; G Naidu; A Deshpande; H Handa; V Raghuvanshi; M Gupta (Wolters Kluwer Medknow Publications, 2018)
Background: A double-blind randomized control trial was conducted to compare the clinical efficacy of topical triamcinolone acetonide 0.1% and amlexanox 5% in recurrent apthous stomatitis (minor). Materials and Methods: Forty adult patients were assessed for erythema, ulcer size, pain scores, and ulcer healing on three evaluation visits within 24 h of ulcer formation, third day, and fifth day. All participants were monitored for compliance with treatment protocols of four times daily application of calibrated quantity of medication. Results and Discussion: Ninety percent of controls when compared with 65% of the participants in the amlexanox group showed complete improvement of peri-ulcer erythema. Pain reduction was marked from the first to the fifth day (F = 15.249, P = 0.000). The control participants showed 90% reduction in pain in comparison to 70% in the amlexanox group. The mean ulcer size was shown to reduce from the first to fifth day in both groups (F = 18.611, P = 0.000). Completely healed ulcers were seen in 70% of the participants in the control group compared with 75% of the participants in the amlexanox group. Conclusion: The data suggest that the clinical efficacy of topical amlexanox 5% is comparable to topical 0.1% triamcinolone acetonide and may be considered a substitute except in pain control, which was marginally less for the treatment for recurrent apthous stomatitis (minor).